Lactobacillus plantarum HY7712 Ameliorates Cyclophosphamide-Induced Immunosuppression in Mice - Jang, S.E., Kyung Hee University, Seoul, Republic of korea; Joh, E.H., Kyung Hee University, Seoul, Republic of korea; Lee, H.Y., Korea Yakult Co., Ltd., Yongin, Republic of Korea; Ahn, Y.T., Korea Yakult Co., Ltd., Yongin, Republic of Korea; Lee, J.H., Korea Yakult Co., Ltd., Yongin, Republic of Korea; Huh, C.S., Korea Yakult Co., Ltd., Yongin, Republic of Korea; Han, M.J., Kyung Hee University, Seoul, Republic of korea; Kim, D.H., Kyung Hee University, Seoul, Republic of korea (Journal of microbiology and biotechnology, 2013)
Lactic acid bacteria (LAB) in fermented foods have attracted considerable attention recently as treatment options for immune diseases, the incidence of which has been increasing worldwide. The ability of 500 strains of LAB, isolated from kimchi, to induce TNF-α production in peritoneal macrophages was investigated. Lactobacillus plantarum HY7712 most strongly induced TNF-α production as well as NF-κB activation. However, HY7712 inhibited NF-κB activation in LPS-stimulated peritoneal macrophages. When HY7712 was orally treated in cyclophosphamide (CP)-immunosuppressed mice for 5 or 15 days, it reversed the body and spleen weights, blood RBC and WBC levels, and splenocyte and bone marrow cells that were reduced by CP. Orally administered HY7712 increased concanavalin A-induced T cell proliferation to 84.5% of the normal group on day 15, although treatment with CP alone markedly reduced it to 53.7% of the normal group. Furthermore, orally administered HY7712 significantly induced the expressions of IL-2 and IFN-γ in ConA-induced splenic cytotoxic T cells of CP-treated mice. Orally administered HY7712 restored the CP-impaired phagocytosis of macrophages in mice. Orally administered HY7712 also restored the cytotoxicity of NK and cytotoxic T cells derived from spleen and bone marrow against YAC-1 in CP-immunosuppressed mice. Based on these findings, orally administered HY7712 may accelerate the recovery of cyclophosphamide-caused immunosuppression, without evident side effects, by immunopotentiating NK and Tc cells, and may provide a mechanistic basis for using HY7712 as an alternative means in lessening chemotherapyinduced immunosuppression in cancer patients.